Enhanced production of highly methylated brGDGTs linked to anaerobic bacteria from sediments of the Mariana Trench - Zeng, Zhiyu; Xiao, Wenjie; Zheng, Fengfeng; Chen, Yufei; Zhu, Yuanqing; Tian, Jiwei; Zhang, Chuanlun (Frontiers in Marine Science, 2023)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial membrane lipids that are widely used in terrestrial paleoclimatic reconstructions. Recent studies have reported that brGDGTs can also be produced by marine bacteria. However, the environmental factors influencing marine-derived brGDGTs and their source organisms remain largely unknown. Here, we investigated the distribution and composition of brGDGTs and a suite of their putative derivatives called overly branched GDGTs (obGDGTs) in the Mariana Trench core sediments (water depth 8300 m, core length 320 cm), as well as the composition of bacterial communities. The ratio of the branched over isoprenoid tetraethers (BIT) was 0.03-0.21 (average 0.07; SD = 0.04; n = 21) and the ratio ΣIIIa/ΣIIa of brGDGTs was 0.93-7.47 (average 3.39; SD = 1.73; n = 21), which support the in situ production of brGDGTs. Co-occurrence network analysis revealed that a total of 33 types of bacteria at the order level (e.g., Armatimonadota DG-56, Proteobacteria Rhodospirillales, Chloroflexi SAR202_clade) were closely related to the distribution of brGDGTs and obGDGTs, which could be potential sources for these compounds. The abrupt increase in brGDGT and obGDGT concentrations in deeper oxygen-depleted sediments and their good correlations with anaerobic bacterial abundances suggest that these brGDGTs and obGDGTs may be produced by anaerobic bacteria residing in the anoxic sediments. Considerable variation in the degrees of methylation and cyclization of brGDGTs (obGDGTs) under different redox conditions indicate that sediment oxygen levels may have a profound impact on the presence and abundance of brGDGTs and obGDGTs, which should be considered when applying them for paleo-temperature or pH reconstructions. This study shows that brGDGTs and obGDGTs obtained from the Mariana Trench were probably produced by a variety of bacterial phyla indigenous in the hadal ocean, which are different from Acidobacteria commonly considered to be major terrestrial sources of brGDGTs.